Improving Mathematics Learning Outcomes of Fifth Grade Elementary School Students through the STAD Cooperative Model on Fractions - Guesa Maiwinda; Marzia Herawati; Dorisno Dorisno (International Journal of Education, Language, and Social Science, 2026)
This study aims to determine whether the Student Teams Achievement Division (STAD) cooperative learning model improves fifth-grade students' mathematics learning outcomes in adding fractions with different denominators. This study used a classroom action research (CAR) design conducted in two cycles, involving 19 students of SDN 03 Pulai Anak Air, Bukittinggi. Data were collected through learning achievement tests and structured observations of student activities. The results showed a measurable increase in student learning outcomes. The percentage of students achieving mastery increased from 60.87% in Cycle I to 78.26% in Cycle II, while the average score increased from 71.39 to 77.13. In addition, student learning activities showed an increase from 51.33% to 58.5% in both cycles. These findings indicate that the implementation of the STAD model positively contributes to both cognitive achievement and student engagement in mathematics learning.